2019
DOI: 10.1002/adfm.201805822
|View full text |Cite
|
Sign up to set email alerts
|

Strong Damping‐Like Spin‐Orbit Torque and Tunable Dzyaloshinskii–Moriya Interaction Generated by Low‐Resistivity Pd1−xPtx Alloys

Abstract: Despite their great promise for providing a pathway for very efficient and fast manipulation of magnetization, spin-orbit torque (SOT) operations are currently energy inefficient due to a low damping-like SOT efficiency per unit current bias, and/or the very high resistivity of the spin Hall materials. This work reports an advantageous spin Hall material, Pd 1−x Pt x , which combines a low resistivity with a giant spin Hall effect as evidenced with three independent SOT ferromagnetic detectors. The optimal Pd … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 44 publications
8
81
0
Order By: Relevance
“…The nonvolatile SOT-MRAMs can have long data retention, zero standby power, and fast and reliable write. 35). [1] Recent harmonic response measurements on Au 1−x Pt x /Co bilayers [18,19] have indicated that the Au 0.25 Pt 0.75 alloy can be a particularly compelling spin Hall metal for energy-efficient SOT applications due to the combination of a relatively low resistivity (ρ xx ≈ 80 µΩ cm) with a strong antidamping SOT efficiency (ξ DL j ≈ 0.3-0.…”
Section: Energy-efficient Ultrafast Sot-mrams Based Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonvolatile SOT-MRAMs can have long data retention, zero standby power, and fast and reliable write. 35). [1] Recent harmonic response measurements on Au 1−x Pt x /Co bilayers [18,19] have indicated that the Au 0.25 Pt 0.75 alloy can be a particularly compelling spin Hall metal for energy-efficient SOT applications due to the combination of a relatively low resistivity (ρ xx ≈ 80 µΩ cm) with a strong antidamping SOT efficiency (ξ DL j ≈ 0.3-0.…”
Section: Energy-efficient Ultrafast Sot-mrams Based Onmentioning
confidence: 99%
“…For example, for the pulse width of 200 ps (1 ns), the required switching current for the Au 0.25 Pt 0.75 device is 6I ∞ (2I ∞ ), markedly smaller than 90I ∞ (20I ∞ ) predicted by the macrospin simulation (see Figure 2b). There is also strong interfacial Dzyaloshinskii-Moriya interaction (DMI) [35] and magnetic roughness (variations of thickness and interfacial magnetic anisotropy field) [22] at the Pt (alloy)/ FM interfaces, which should enhance the magnetic nonuniformity. Here, we attribute the observed ultrafast switching mainly to the enhanced nonuniform micromagnetic dynamics within the free layer of our devices.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…DL for Pt/ferromagnet (FM) systems is ~0.08 where ρxx = 20 μΩ cm [16]. Recently, impurity scattering has been demonstrated to increase DL via enhancing ρxx [17][18][19][20]. However, in all the previous work the increase of DL was limited (e.g., to DL = 0.12-0.3 for 4 nm Pt alloys) due to a fast decrease in σSH with doping level [19] or/and only a weak enhancement of ρxx [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, impurity scattering has been demonstrated to increase DL via enhancing ρxx [17][18][19][20]. However, in all the previous work the increase of DL was limited (e.g., to DL = 0.12-0.3 for 4 nm Pt alloys) due to a fast decrease in σSH with doping level [19] or/and only a weak enhancement of ρxx [17,18]. Exploring new enhancement strategies that can better optimize the trade-offs between ρxx and TintσSH is of both fundamental interest and technological urgency (e.g., for low-power magnetic memories, logic, and oscillators).…”
Section: Introductionmentioning
confidence: 99%
“…Here θSH is the spin Hall ratio of the HM. For SOT experiments [20][21][22][23], the drift-diffusion analysis [4,17] predicts an interfacial spin transparency [19] Tint = 2 eff ↑↓ /GHM ≤ 1 (2) when the HM thickness d >> λs and the interfacial spin-orbit coupling (ISOC) is negligible. Therefore, the measured dampinglike SOT efficiency per unit applied electric field is DL ≈ 2 eff ↑↓ θSH/ρxxGHM.…”
mentioning
confidence: 99%